Her Mother's Hope - Rivers, Francine 1947- (Carol Stream, Ill. : Tyndale House Publishers, 2010)
Marta, who left Switzerland to find her own way in the world, must come to terms with her faulty yet well-meaning desire to help her daughter, Hildie, find her place, as Hildie becomes a nurse and has a family of her own.
Keywords: Mother-daughter relationship -- Fiction; Self-realization -- Fiction; Bildungsromans; Fiction